2002
DOI: 10.1007/s00412-001-0175-z
|View full text |Cite
|
Sign up to set email alerts
|

Trends in site-number change of rDNA loci during polyploid evolution in Sanguisorba (Rosaceae)

Abstract: To elucidate the evolutionary dynamics of rDNA site number in polyploid plants, we determined 5S and 18S-5.8S-26S rDNA sites for ten species of Sanguisorba (2n=14, 28, 56) and a single species of each of three outgroup genera, Agrimonia (2n=28), Rosa (2n=14), and Rubus (2n=14) by the fluorescence in situ hybridization (FISH) method. We also estimated phylogenetic relationships among these species using matK chloroplast DNA (cpDNA) sequences, and reconstructed the evolutionary history of rDNA site number based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
70
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 39 publications
10
70
2
Order By: Relevance
“…The diploid and tetraploid chromosome numbers conformed the previous reports from Eastern and Western Himalayas by the various workers, whereas the hexaploid chromosome number is newly reported. For genus Agrimonia, the lowest chromosome number is reported to be nϭ14, and the presently as well as previously worked out euploid cytotypes are all multiples of xϭ14, supporting the observations of Mishima et al (2002) and Malin (2004). Hence, the presently worked out materials are designated as 2x, 4x and 6x.…”
Section: Discussionsupporting
confidence: 82%
“…The diploid and tetraploid chromosome numbers conformed the previous reports from Eastern and Western Himalayas by the various workers, whereas the hexaploid chromosome number is newly reported. For genus Agrimonia, the lowest chromosome number is reported to be nϭ14, and the presently as well as previously worked out euploid cytotypes are all multiples of xϭ14, supporting the observations of Mishima et al (2002) and Malin (2004). Hence, the presently worked out materials are designated as 2x, 4x and 6x.…”
Section: Discussionsupporting
confidence: 82%
“…Possibly, paracentric 5S rDNA loci were lost from marker chromosomes 3 and 4 during the evolution of the Caninae. The presence of two 5S rDNA loci per genome in the diploid species R. multiflora (Mishima et al, 2002) and one 18S-26S rDNA locus per genome in most of the rose species investigated by Ma et al (1997) and Fernandez-Romero et al (2001) is consistent with this argument. Ma et al (1997) found one 18S-26S rDNA locus per genome, located terminally on the short arms of small submetacentric chromosomes, in five diploid species and one tetraploid cultivar of Rosa.…”
Section: Discussionsupporting
confidence: 55%
“…However, polymorphism of both rDNA loci number and position has been observed in many plant species, limiting the application of rDNA as reliable chromosome landmarks. Such intraspecific variation in number and chromosomal distribution of rDNA loci has been reported in numerous plant genera, including Brassica, Raphanus, Sinapis [14], Pinus [15] and Sanguisorba [16]. The number and chromosomal distribution of rDNA loci have also been analysed in some species of Brachypodium [17,18].…”
Section: Introductionmentioning
confidence: 82%